To translate the line defined by the equation \( y = 3x + 2 \) one unit to the right and two units up, we need to adjust the equation accordingly.
-
Translate one unit to the right:
- Shifting a line to the right involves replacing \( x \) with \( x - 1 \). So, we replace \( x \) in the original equation: \[ y = 3(x - 1) + 2 \] Simplifying this: \[ y = 3x - 3 + 2 \] \[ y = 3x - 1 \]
-
Translate two units up:
- To shift the line up, we add 2 to the \( y \) value: \[ y = 3x - 1 + 2 \] Simplifying this: \[ y = 3x + 1 \]
Thus, the equation of the new line after the translation is:
\[ \boxed{y = 3x + 1} \]